Spectroscopic determination of velocity dispersion lens galaxies and their impact on the measurement of the post-Newtonian parameter - Beloto, Ingrid; Cypriano, Eduardo; Makler, Martin (Cadernos de Astronomia, 2024)
This study is dedicated to making precise measurements of the velocity dispersion of lens galaxies, using data obtained by the SOuthern Astrophysical Research (SOAR) telescope during the year 2022. From the analysis of 10 galaxy spectra, we obtained fundamental estimates of their velocity dispersions. speed. This work provides crucial measurements that will be used in collaboration with researchers at the Brazilian Center for Physical Research to infer the post-Newtonian parameter γ. This partnership aims to improve the accuracy of future estimates of this parameter, significantly contributing to the understanding of the fundamental laws of gravity on galactic scales through the mass comparison method, by comparing the dynamic mass of galactic gravitational lenses, independent of γ , with the mass obtained through lens modeling, which depends on γ.